A new textile sizing prepared by the hemp core cellulose ethers - Zhang Xin; Ji Yingchao; Wang Ying; Wang Qiuhong; Zhang Qingli; Yu Zhihua (Functional Materials, 2016)
As the key process of weaving, sizing is one of the processes which are of great costly and serious pollution in the whole cotton-textile production. Great efforts have been made to study new kinds of sizing to reduce costs and environment pollution. In this paper, hemp cellulose ethers of Methyl cellulose (MC) ether and Hydroxypropyl methyl (HPMC) cellulose ether further were used as a kind of textile sizing. The results indicated that the MC and HPMC blended by 1:1 of sizing efficiency was similar to thos e of PVA. After sizing with this new kind of size, the breaking strength and elongation at break could replace sizing property of PVA, even extending beyond PVA. Compared to COD in the desizing wastewater of 30240 mg/L of PVA, the COD of hemp cellulose ether sizing was very small of 13235.2 mg/L. Therefore, it is concluded that the hemp core ether is a new and environment-friendly textile sizing, which has low cost and contributes a healthier ecosystem